An Ethnographic Account of Reiki Practice in Britain. - Beeler, Dori-Michelle (Cambridge Scholars Publishing, 2016)
An Ethnographic Account of Reiki Practice in Britain is the result of 14 months of ethnographic research. This study, while filling a gap in the qualitative literature on Reiki practice, contributes an ethnographic portrayal of a particular group's construction of well-being. Contributing to medical anthropology, the research findings demonstrate culturally situated ideas and practices related to health wherein the intersubjective nature of healing is a constitutive element for well-being. The distinctions of this are specific to culture and environment, broadening how spirituality and well-be.